2022
DOI: 10.3390/ijms232214229
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Male Reproductive Toxicity of Polybrominated Diphenyl Ethers

Abstract: Polybrominated diphenyl ethers (PBDE) are a group of flame retardants used in a variety of artificial materials. Despite being phased out in most industrial countries, they remain in the environment and human tissues due to their persistence, lipophilicity, and bioaccumulation. Populational and experimental studies demonstrate the male reproductive toxicity of PBDEs including increased incidence of genital malformations (hypospadias and cryptorchidism), altered weight of testes and other reproductive tissues, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 214 publications
1
5
0
Order By: Relevance
“…Additionally, BDE-47 reduced gene expression in the gonadal and growth hormone pathways. Both results are concordant with previously reported effects of BDE-47 on reproductive outcomes 23 and IGF-1 in circulation 19,28 . Figure 8 summarizes the gene and gene pathway effects of BPS (A) and BDE 47 (B).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, BDE-47 reduced gene expression in the gonadal and growth hormone pathways. Both results are concordant with previously reported effects of BDE-47 on reproductive outcomes 23 and IGF-1 in circulation 19,28 . Figure 8 summarizes the gene and gene pathway effects of BPS (A) and BDE 47 (B).…”
Section: Discussionsupporting
confidence: 93%
“…Although, commercial use of PBDE has ceased in many developed countries, their concentrations remain high in human samples in the North America 16,17 . Developmental exposures to BDE-47 in laboratory animals and humans result in the disruption of lipid and carbohydrate metabolism [18][19][20][21][22] , and deterioration of reproductive health 23 and impairment of cognitive development 24,25 . PBDEs are known also to disrupt multiple endocrine mechanisms, including the direct interaction with hormonal receptors, transporting proteins, and the induction of metabolic enzymes responsible for the metabolism of hormones 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PBDE-71 significantly increased malformation and the percentage of males in the F1 generation and reduced frequencies of male courtship behaviors [215,216]. Arowolo et al indicated that PBDEs and their metabolites, when present at environmental levels, may impact male reproductive health through AR antagonism, testosterone signaling, cAMP production, mechanistic target of rapamycin complex one (mTORC1) signaling and TH transport [217]. In addition, it appears that PBDE-47 has the potential to enhance the sensitivity of adult Leydig cells to cAMP when synthesizing androgen [218].…”
Section: Othersmentioning
confidence: 99%
“…92 Some studies have reported a negative association between seminal fluid or serum PBDE levels and sperm motility, morphology, concentration, or total sperm count, while other studies have found no significant association. [133][134][135][136][137][138][139] However, the number of available studies is limited, and the results are heterogenous. 80…”
Section: Polybrominated Diphenyl Ethersmentioning
confidence: 99%